LANGUAGE POLICY AND THE BERBER ISSUE IN THE MAGREB COUNTRIES - Kadyrova Mashkhura Mirzaakbarovna (Journals Park Publishing, 2023)
The article examines the features of language policy pursued in the countries of North Africa as well as problems of a national-ethnic nature. Despite being little studied, this topic is still the subject of research by orientalists and Arabists around the world. The article also discusses issues of language policy and the problems of bilingualism and multilingualism in this region.
Keywords: language conflicts, Arabization, dialects, Frenchization, billingism, language policy, Berber question.